Identification, Pathogenicity, and Antimicrobial Resistance Analysis of Bacterial Pathogenesis Aeromonas hydrophila from Hybrid Sturgeon (Huso dauricus ♀ × A. schrenckii ♂) in Zhejiang, China - Haojie Hu; Xinzhi Weng; Gang Pang; Xiaobing Li; Jing Xia; Xiu Gao; Jie He; Ji Li; Dong Qian (Microorganisms)
In 2019, a disease outbreak struck a hybrid sturgeon farm (Huso dauricus ♀ × A. schrenckii ♂) in Tiantai, Zhejiang province, leading to the deaths of 8000 sturgeons. The sturgeons exhibited reduced appetite, lethargic and uncoordinated swimming, and physical signs such as reddish petechiae and ulcers on the body and fins. Hemorrhagic spots were observed on the kidneys, spleen, and gonads, alongside reddish intestines with hemorrhagic ascites in the abdominal cavity. ST-1902 was isolated and identified as Aeromonas hydrophila through physiological and biochemical characterization and 16S rDNA sequence analysis. The pathogenicity of ST-1902 was confirmed through a challenge test, with a median lethal dosage (LD50) of 7.9 × 106 CFU/IND. Histopathological examination showed hyperplasia and neoplasm-like changes in the epicedial mesothelial tissues, enlarged and necrosis renal tissue, and serious hemosiderosis in spleen and gills. Virulent genes (Aer, Epa, Alt, Hly, and Act) were detected in ST-1902, corresponding to typical β-hemolysis, extracellular protease, and enterotoxin. Moreover, antimicrobial experiment detection indicated ST-1902 is sensitive to quinolones and phenicols but resistant to sulfamethoxazole, aminoglycoside antibiotics with Sul1, and Intl and Ant (3”)-I. These results suggest that A. hydrophila was the causative agent of the sturgeon disease and highlight the emerging threat it poses to the sturgeon industry.